THE EFFICIENCY OF UPSKILLING GRADUATE DIPLOMA STUDENTS AT MALAYSIAN VOCATIONAL COLLEGES IN 3G SMAW WELDING WORK – A CASE STUDY - Nurul Aini Mohd. Ahyan; Nur Shahirah Mohamed Nasir; Mohd Rafi Muhamad; Nur Hazirah Noh@Seth (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This article examines the effectiveness of upskilling initiatives for Graduate Diploma students in vocational colleges in Malaysia. Thirty Kolej Vokasional Tanjung Piai graduates who took a 3G SMAW (Shielded Metal Arc Welding) course at CIDB Technologies Sdn Bhd, Johor are the focus of this case study. In a rapidly evolving industrial setting, the study aims to assess the degree to which the upskilling program enhanced the participants’ overall employability and welding skills. Survey data showed that participants were satisfied with the upskilling program’s content, emphasizing how applicable it was to their professional growth and the useful skills they had learned. Additionally, participants offered insightful comments that suggested a number of improvements to boost the training’s efficacy, including greater practical experience, easier access to contemporary equipment, and more thorough safety instruction. The results highlight how crucial it is for vocational education programs to be continuously improved in order to satisfy industry expectations and give graduates employable skills.